Cyclical Vomiting Syndrome in Children: Potential Role of Electroencephalogram in the Diagnostic Evaluation - TAN LI NIEN (Wolters Kluwer - Medknow, 2021)
International Journal of Gastroenterology, Hepatology, Transplant & Nutrition